2022
DOI: 10.3389/fsurg.2022.898243
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic Effect of the Fascia Iliaca Compartment Block with Different Approaches on Total Hip Arthroplasty and Its Effect on Postoperative Cognitive Dysfunction and Inflammation

Abstract: ObjectiveThe objective of this article is to make a comparison of the anesthetic effects of the inside and outside fascia iliaca compartment block (FICB) in total hip arthroplasty (THA) and to study the effect of the different approaches of the FICB on postoperative cognitive dysfunction (POCD) and serum inflammatory cytokines in THA patients.MethodsA total of 60 patients who received THA treatment from January 2021 to December 2021 were divided into two groups, namely, Inside group (inside approach of the FIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Serum levels of IL-1β at 1 and 6 h post-surgery and IL-6 levels at 1, 6, 24, and 48 h were significantly higher in the Outside group than in the Inside group. The study concluded that the inside approach of the FICB demonstrated better anesthetic effectiveness, improved postoperative analgesia, reduced need for postoperative analgesics, lower incidence of POCD, and decreased serum cytokine levels in patients undergoing THA than the outside approach [237].…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Serum levels of IL-1β at 1 and 6 h post-surgery and IL-6 levels at 1, 6, 24, and 48 h were significantly higher in the Outside group than in the Inside group. The study concluded that the inside approach of the FICB demonstrated better anesthetic effectiveness, improved postoperative analgesia, reduced need for postoperative analgesics, lower incidence of POCD, and decreased serum cytokine levels in patients undergoing THA than the outside approach [237].…”
Section: Resultsmentioning
confidence: 94%
“…NLRP3 is a newly discovered factor associated with the progression of many diseases and may be related to inflammation [236]. Feng T. et al assessed the role of FICB and postoperative cognitive dysfunction and serum inflammatory cytokines in a recent published study on patients that underwent total hip replacement surgery [237]. All enrolled patients underwent general anesthesia with endotracheal intubation and an FICB that was performed with an ultrasound-guided inside approach (Inside group) or outside approach (Outside group).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study, after blocking, PSQI and MMSE scores decreased in both groups, and PSQI score in group P was lower than that in group F, MMSE score in group P was higher than group F, revealing that the both blocks could improve the sleep quality of the elderly and play a certain protective effect on their neurological function, but the effect of PENG block was more significant. The possible mechanisms of the protective effect of nerve block on cognitive function are as follows: regional block can significantly reduce the dosage of general anesthesia drugs, reduce the concentration of inhaled anesthesia drugs, and thus, reduce the neurotoxic effects of general anesthesia drugs; regional block can reduce the stress of surgical trauma and pain on the whole body, inhibit the inflammatory response of the central nervous system, reduce the damage of the central nervous system, and thus protect the cognitive function 20 .…”
Section: Discussionmentioning
confidence: 99%
“… 14 Feng et al compared the effect of different approaches to the fascia iliaca compartment block on POCD in THA patients. 15 It has also been demonstrated that elderly patients with type A blood had a higher risk of developing early POCD than those with type O blood. 16 Nevertheless, little is known about the comprehensive intervention methods to reduce POCD in THA patients from various aspects.…”
Section: Introductionmentioning
confidence: 99%